2009
DOI: 10.1016/j.cell.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The BRC Repeats of BRCA2 Modulate the DNA-Binding Selectivity of RAD51

Abstract: SUMMARY The breast cancer susceptibility protein, BRCA2, is essential for recombinational DNA repair. BRCA2 delivers RAD51 to double-stranded DNA (dsDNA) breaks through interaction with eight conserved, ~35 amino acid motifs, the BRC repeats. Here we show that the solitary BRC4 promotes assembly of RAD51 onto single-stranded DNA (ssDNA), but not dsDNA, to stimulate DNA strand exchange. BRC4 acts by blocking ATP hydrolysis and thereby maintaining the active ATP-bound form of the RAD51-ssDNA filament. Single-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
260
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(275 citation statements)
references
References 34 publications
15
260
0
Order By: Relevance
“…To investigate the molecular mechanism underlying p53(WT)-mediated recombination stimulation, we silenced factors implicated in the bypass of blocked replication forks. p53 inhibits the helicase and the branch-migrating activities of Bloom syndrome protein (BLM) and Werner syndrome protein (WRN) helicases, which are involved in the regulation of HR and in the bypass of replication barriers (32,33), whereas RAD51 and breast cancer 2 (BRCA2) are involved in HR-dependent postreplication repair (34,35). Proliferating cell nuclear antigen (PCNA)-associated recombination inhibitor (PARI) associates with DNA damage sites via SUMOylated PCNA and blocks recombination by inhibition of RAD51-DNA filament formation (36).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the molecular mechanism underlying p53(WT)-mediated recombination stimulation, we silenced factors implicated in the bypass of blocked replication forks. p53 inhibits the helicase and the branch-migrating activities of Bloom syndrome protein (BLM) and Werner syndrome protein (WRN) helicases, which are involved in the regulation of HR and in the bypass of replication barriers (32,33), whereas RAD51 and breast cancer 2 (BRCA2) are involved in HR-dependent postreplication repair (34,35). Proliferating cell nuclear antigen (PCNA)-associated recombination inhibitor (PARI) associates with DNA damage sites via SUMOylated PCNA and blocks recombination by inhibition of RAD51-DNA filament formation (36).…”
Section: Resultsmentioning
confidence: 99%
“…The NPF is responsible for DNA sequence homology recognition in a duplex DNA, usually the sister chromatid, and formation of a joint intermediate that will serve as a priming site for DNA synthesis needed to copy the missing information (Benson et al , 1994). In the cell, HR is tightly regulated, for example by the tumour‐suppressor protein BRCA2 (Sung & Klein, 2006), which is known to mediate the loading of hRAD51 onto RPA‐coated ssDNA, making use of its ability to bind hRAD51 with its BRC‐repeat domain (Wong et al , 1997; Chen et al , 1998; Carreira et al , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we examined a BRC4 mutant, Δ7BRC4, which lacks seven conserved amino acid residues (1524-FHTASGK-1530) that are necessary to bind RAD51 (16) (Fig. 1A, module I).…”
Section: Significancementioning
confidence: 99%
“…We have previously shown that the BRC repeats of BRCA2 modulate the DNA binding selectivity of RAD51 to stimulate the assembly on ssDNA by inhibiting its ATP hydrolysis and preventing its association with dsDNA (2,11,16); as a result, BRCA2 catalyzes the recombination activity of RAD51 (17).…”
mentioning
confidence: 99%